Development Of A Flexible Stable Mammalian Antibody Expression Pipeline - Mark Kar Kei, Jacqueline (2023)
Mammalian antibodies are promising tools for biopharmaceutical use because of their high specificity and low toxicity. These proteins are favorable for both therapeutic and diagnostic purposes and its ever-growing demand calls for high productivity cell lines. Mammalian cell lines can express antibodies transiently or stably. Although the transient expression system has the benefits of rapid production, it is more suitable for short-term protein production and the initial phase of antibody testing. Meanwhile, a stable expression system is the go-to for long-term mass protein production because of its ability to express proteins in a reproducible, scalable, and reliable manner with no batch-to-batch variation.